ANALYSIS OF GOVERNMENT COMMUNICATION REGARDING TERRESTRIAL TELEVISION DIGITALIZATION POLICY IN INDONESIA BASED ON SOCIAL REALITY THEORY - Desliana Dwita (Jurnal Komunikasi, 2024)
The migration policy of the Indonesian government from analogue to digital communication technology for terrestrial television illustrates how government actions in conveying policies intersect with public and private interests. Using Luckmann's theory of social construction of reality, this paper highlights the importance of communication between three stakeholders, i.e., the government, television broadcasting companies, and the public, particularly in policy formulation and implementation. To conduct this study, we used a qualitative method involving in-depth interviews with ten informants, representing the three communication actors. The findings of this study show that since the policy was formulated until its implementation, communication between the government, private sector, and the public has not been effective because the government, broadcasting stakeholders, and the people do not have the same meaning construction about the terrestrial television digitalization policy. Policy implementation often experiences obstacles and delays, failing to meet the initial target, due to changing strategies and regulations. In conclusion, we argue for the need to integrate the principles of good governance into any government communication and policy implementation